Mortality Data Management at Muhammadiyah University Hospital Malang - Untung Slamet Suharyono; Rokhman Handoyo; Farah Naila Rahmatika Orisa Sativa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Background: Mortality data is an important indicator of hospital performance, used for assessment and policy-making. This study evaluates the processing of mortality data at RSU Universitas Muhammadiyah Malang, including recording, coding, and reporting. Methods: A qualitative study with interviews of coding staff and observation of medical records. Results: The recording of death data is suboptimal due to an inappropriate death certificate format. Coding and reselection of UCOD are not optimal because they are not based on the diagnosis in the death certificate, and the UCOD reselection and MMDS rules have not been used. Reporting is done by calculating GDR and NDR, and documenting the diagnoses of deceased patients and KLB reports. Conclusion: Suboptimal management of death data affects data accuracy. SOP creation, redesign of death certificate forms, and training for relevant staff are needed.